Radiocarbon as a biomarker of urban pollution in leaves of evergreen species sampled in Rome and in rural areas (Lazio—Central Italy) - Alessio, M.; Anselmi, S.; Conforto, L.; Improta, S.; Manes, F.; Manfra, L. (Atmospheric Environment, 2002)
The aim of the present study is the use of 14 C, sampled in leaves of evergreen species, as a natural geochemical marker to estimate the contribution of artiﬁcial sources (heating plants, vehicles, etc.) to the complex of atmospheric gases in an urban environment. Leaves were chosen due to sampling easiness and their reliability: in particular the evergreen species, being exposed all the year round to pollutants are especially indicated for bioindication and biomonitoring studies. The response to atmospheric pollutants has been studied of two plant species (Quercus ilex L., Pinus pinea L.) measuring isotopic ( 14 r, d 13 C), chemical (Pb concentration) and ecophysiological (gaseous exchange and leaf ﬂuorescence of chlorophyll a) parameters. Leaves of holm-oaks and stone pine needles collected over a 3-year time span in an urban park in Rome (Villa Ada) and in reference localities outside the city on the Tyrrhenian coast and in the preAppennine area have been analysed. In Villa Ada measurements were carried out along a transect from the road bordering the park towards the interior; all the parameters, together in agreement, showed a decreasing pollution gradient towards the inner park. It was possible to estimate a 5.570.3% contribution of CO2 from fossil fuels close to the road, decreasing to 1.770.3% at o300 m from it towards the inner park. The isotopic analyses conducted on stone pines and holm-oaks show that 14 C provides indications on the degree of pollution from fossil fuels, while d 13 C appears to be conditioned mainly by the interspeciﬁc difference, and also by many other environmental factors that affect the plant functionality. Results conﬁrmed that radiocarbon is a useful tool in environmental studies, allowing to quantify the contributions of CO2 of anthropic origin: this parameter, together with appropriate isotopic, chemicaland ecophysiological analyses, could provide a good indication of the ‘‘air quality’’ in urban and rural contexts.
Keywords: air quality; carbon isotopes; co 2; lead; photosynthesis

Urban Green and Atmospheric Pollution: A Biomonitoring Study on Leaves of Quercus Ilex L. - Anselmi, S.; Giannini, M. A.; Allegrini, I.; Manes, F. (Giornale botanico italiano, 1996)
doi: 10.1080/11263509609439723doi: 10.1080/11263509609439723The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: air quality; atmospheric pollution; leaf functional conditions; Quercus ilex (PG)